2012
DOI: 10.3174/ajnr.a2958
|View full text |Cite
|
Sign up to set email alerts
|

Review of 2 Decades of Aneurysm-Recurrence Literature, Part 2: Managing Recurrence after Endovascular Coiling

Abstract: SUMMARY:Cerebral aneurysms are treated to prevent hemorrhage or rehemorrhage. Angiographic recurrences following endovascular therapy have been a problem since the advent of this treatment technique, even though posttreatment hemorrhage remains rare. Notwithstanding its unclear clinical significance, angiographic recurrence remains not only a prime focus in the literature but also frequently leads to potentially risky retreatments. The literature regarding aneurysm recurrence following endovascular therapy, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…The relatively high recurrence rates after coiling are another major limitation of the endovascular treatment of wide-neck and/or large aneurysms. 2,3 The stent-assisted coiling (SAC) technique was developed to treat wide-neck intracranial aneurysms. 4 Several selfexpandable stents dedicated to intracranial use were introduced in the past decade, and the availability of these self-expandable intracranial stents enabled the endovascular treatment of wideneck complex aneurysms that were uncoilable previously.…”
mentioning
confidence: 99%
“…The relatively high recurrence rates after coiling are another major limitation of the endovascular treatment of wide-neck and/or large aneurysms. 2,3 The stent-assisted coiling (SAC) technique was developed to treat wide-neck intracranial aneurysms. 4 Several selfexpandable stents dedicated to intracranial use were introduced in the past decade, and the availability of these self-expandable intracranial stents enabled the endovascular treatment of wideneck complex aneurysms that were uncoilable previously.…”
mentioning
confidence: 99%
“…Furthermore, it is not absolutely clear as to for how long the aneurysm after endovascular procedures needs to be followed up (18). In the case of adequately occluded aneurysms upon control DSA after six months, further MR angiographies are considered to be an appropriate follow-up imaging tool (19). To date, our current policy is to perform a DSA after 6 months followed with serial MR angiographies, even in case of stable results up to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…These results challenge previous studies reporting that aneurysm recurrence occurs mostly within 6-12 months after coil therapy and that follow-up imaging beyond that period is unnecessary. 12,13,26,27 Using 3-T MR angiography, Ferns et al 13 assessed the occurrence of late (> 4.5 years) aneurysm recanalization after coil therapy in a series of 400 patients with 440 aneurysms. The authors reported delayed aneurysm recurrence in 11 patients (2.8%), with only 3 lesions (0.7%) requiring further treatment.…”
Section: Discussionmentioning
confidence: 99%